2010
DOI: 10.3324/haematol.2010.030957
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic risk stratification in chronic myelomonocytic leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe prognostic value of cytogenetic findings in chronic myelomonocytic leukemia is unclear. Our purpose was to evaluate the independent prognostic impact of cytogenetic abnormalities in a large series of patients with chronic myelomonocytic leukemia included in the database of the Spanish Registry of Myelodysplastic Syndromes. Design and MethodsWe studied 414 patients with chronic myelomonocytic leukemia according to WHO criteria and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
249
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(277 citation statements)
references
References 21 publications
14
249
4
4
Order By: Relevance
“…Patients with SF3B1 mutations did have a higher % of BM RS, lower median white count and a lower ALC, perhaps indicators of less aggressive disease. There were no differences in the distribution of patients across the Spanish cytogenetic risk stratification and the MDAPS risk categories [23,24].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Patients with SF3B1 mutations did have a higher % of BM RS, lower median white count and a lower ALC, perhaps indicators of less aggressive disease. There were no differences in the distribution of patients across the Spanish cytogenetic risk stratification and the MDAPS risk categories [23,24].…”
Section: Discussionmentioning
confidence: 88%
“…All BM slides, including iron stains for quantification of BM RS were centrally reviewed. Karyotype risk designation and risk stratification were according to the Spanish cytogenetic risk stratification system [23] and the MD Anderson prognostic scoring system (MDAPS) [24], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The chronic myelomonocytic leukemia karyotypes were also stratified according to the IPSS scoring system, 21 the new Comprehensive Cytogenetic Scoring System (CCSS) for primary myelodysplastic syndrome, 22 and the recently proposed cytogenetic risk stratification system for chronic myelomonocytic leukemia. 23 The CCSS score was also used along with blood counts and bone marrow blast count to classify the chronic myelomonocytic leukemia cases according to the IPSS-R scoring system. 17 NPM1 and FLT3 Mutation Analysis NPM1 and FLT3 mutation status was obtained from available molecular diagnostic reports of acute myeloid leukemia, myelodysplastic syndrome, and chronic myelomonocytic leukemia cases.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Clinical parameters, such as older age, low hemoglobin level, high WBC count, presence of IMC, and high percentage of bone marrow blasts have been reported to be associated with an inferior survival [2,[7][8][9][17][18][19][20]. Recently, cytogenetic data and gene mutations have been recognized as important prognostic factors and incorporated into the CMML risk stratification system [1,8,11,20].…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic abnormalities are detected in about 20-40% of CMML patients at the time of diagnosis [1][2][3][4][5][6][7][8][9][10][11] and have been shown to be prognostically relevant [1,[7][8][9][10][11]. In an earlier study [1], we found that CMML patients with an abnormal karyotype had a poorer overall survival (OS) compared with patients who had a normal karyotype.…”
Section: Introductionmentioning
confidence: 99%